The Management of a PLE from the Perspective of Higher Education Students - Costa, Fernando Albuquerque (2012)
This paper presents the results of an exploratory study. The goal is to understand the nature of the difficulties faced by higher education students, when they are encouraged to use methodologies based on the use of online Personal Learning Environments (PLE). Two groups of 2nd-year degree students were surveyed through a questionnaire, in two different academic years, as part of a curricular subject that promotes a working strategy based on the presentation and discussion of theoretical content in the classroom, and additionally on the undertaking of tasks outside a face-to-face context, involving students exploring the potential of the Internet and the social software. Analysis of the results led to the conclusion that, despite the students recognising, in general, that the undertaking of PLE depends largely on themselves, namely the organisation and management strategies they implemented, they did not feel prepared for this type of learning. The students experienced difficulties in personal organisation, the adoption of continuous and systematic working methods, participation in the tasks set and completion of the learning tasks. To overcome these difficulties, the students preferred to ask the teacher about their doubts rather than to interact with their classmates, and use the different tools and technologies available online. The conclusion was that preparatory work must be undertaken in advance to encourage the creation and use of personal online environments as a learning method in higher education, aimed at fostering competencies such as autonomy in learning, the ability to reflect and the capacity for critical analysis of the students’ own output.